Human milk biochemistry and infant formula manufacturing technology - Guo, Mingruo, 1960- (Woodhead Publishing, 2014)
Since infant formula substitutes for human milk, its composition must match that of human milk as closely as possible. Quality control of infant formula is also essential to ensure product safety, as infants are particularly vulnerable food consumers. This book reviews the latest research into human milk biochemistry and best practice in infant formula processing technology and quality control. The most up to date reference on infant formula processing technologyReviews both human milk biochemistry and infant formula processing technology for broad and applied coverageFocusses exclusively on in.
Keywords: Infant formulas.; Food -- Biotechnology.; Food industry and trade.; Food science.; elektronické knihy; electronic books